ANALYSIS OF HOUSE WASTE POLLUTION SLAUGHTERING CHICKEN IN THE KEMUNING RIVER - M. Dhiyaul Auliya; M Rahman; R Putri Mahyudin; A Sulaiman (Bajang Institute, 2024)
Poorly managed slaughterhouses can have negative impacts on the environment and on human life. Wastewater from chicken slaughterhouses is very harmful to the environment. This study aimed to analyse the water management and wastewater quality of 3 RPAs (Rambai Timur, Arjuna and Guntung Manggis) where the 3 RPAs flow into the Kemuning River. This study used a qualitative approach with observations, interviews, questionnaires and laboratory tests. The results showed that the wastewater management in the 3 RPAs was not optimal because all wastewater from slaughtering, soaking with hot water for hair removal, processing of internal organs containing blood (intestines and liver), as well as the process of cleaning slaughterhouses and cleaning equipment used in the RPAs is directly discharged without treatment. The effluent quality in the 3 landfills is still in the low category as shown by the fat/oil content, NH3-N (0.05-40) and pH (3.20-6.10), but the BOD (1866.67-11533 mg/L), COD (27.414-12417.04 mg/L) and TSS (129-989 mg/L) are very high and exceed the type 1 effluent quality standard. Meanwhile, the water quality in the Kemuning River is below the wastewater quality standard for slaughterhouses and/or activities based on the Minister of Environment's Regulation No. 5 of 2014. Therefore, the 3 RPAs must pay attention to wastewater management to make it better, RPAs must carry out routine monitoring of wastewater quality, RPA managers must always keep the RPA environment safe from pollution or contamination